The Role of Religiosity on Investment Intention of Muslim Students in Sharia Bank - Firial Dhya Salsabila; Nur Wening; Bambang Moertono, S.; Muhammad Rafi Dhiaulhaq (Syntax Corporation Indonesia, 2023)
The purpose of this study was to examine how religiosity influences the intention to save Muslim students in Islamic banks. The research was conducted with a research population of students in Yogyakarta from several public and private universities. The sampling technique used accidental sampling and obtained 30 respondents. This study uses a data analysis method in the form of simple linear regression. The results of the study stated that there was no effect of student religiosity on interest in investing in Islamic banks. The value of the coefficient of determination (R2) = 0.017. This means that the variable interest in saving moeslim's students in Islamic banks is influenced by religiosity only by 1.7% while the remaining 98.3% is influenced by other variables not examined.